Ortholinea concentrica n. sp. (Cnidaria: Myxozoa) from the Patagonian seabass Acanthistius patachonicus (Jenyns, 1840) (Perciformes: Serranidae) off Patagonia, Argentina - Alama-Bermejo, Gema; Hernández-Orts, Jesús S (Parasitology research, 2018)
The Patagonian seabass Acanthistius patachonicus (Jenyns, 1840) (Serranidae) is a marine fish valued for commercial and sport fisheries from Argentina. We report a new myxosporean (Cnidaria: Myxozoa) infecting the urinary system of the Patagonian seabass from San Antonio Bay, San Matías Gulf, on the Atlantic Ocean. The mature myxospores were subspherical, 8.2-11.0 μm × 7.9-11.0 μm and 7.7-9.0 μm in thickness; two subspherical polar capsules, 2.4-3.8 μm × 2.3-3.6 μm, with 3 to 4 turns of the polar tubule; openings on different valves in almost opposite directions. Ornamented shell valves exhibited 17-20 concentrically organized surface ridges. SSU rDNA phylogenetics analyses placed the new species in the freshwater urinary tract clade, clustering in a clade formed by Myxobilatus gasterostei (Parisi, 1912), Acauda hoffmani Whipps, 2011, and other Ortholinea spp. Based on spore morphology, site of infection, and molecular data, we described this myxozoan as Ortholinea concentrica n. sp.
Keywords: Urinary Tract; Atlantic Ocean; Marine fish; Fish Diseases; močové ústrojí; Argentina; fylogeneze; Phylogeny; ribozomální DNA; Urinary system; Myxozoa; South America; Atlantský oceán; Animals; Percoidea; SSU rDNA; ženské pohlaví; Taxonomy; parazitární nemoci u zvířat; zvířata; nemoci ryb; Parasitic Diseases, Animal; Spores; Bass; spory; DNA, Ribosomal; Female